Transcriptome analysis reveals a positive role for nerve growth factor in retinol metabolism in primary rat hepatocytes. (July 2018) - Kao, Ying-Hsien; Lee, Po-Huang; Chiu, Ting-Chia; Lin, Yu-Chun; Sun, Cheuk-Kwan; Chen, Po-Han; Tsai, Ming-Shian
Highlights: Transcriptome reveals NGF increased 10 genes and decreased 23 genes in hepatocytes. NGF triggered de novo synthesis of RDH16 and affected retinol metabolism pathway. NGF treatment also enhanced RDH16 expression in cholestatic mouse livers. NGF-upregulated RDH16 expression in hepatocytes via an NF-κB-dependent pathway. Abstract: Up-regulation of nerve growth factor (NGF) in parenchymal hepatocytes with cholestatic injury has been previously demonstrated to exert hepatoprotective effects in an autocrine manner; however, the overall impact of NGF up-regulation remains elusive. This study aimed to profile the effects of exogenous NGF on cultured primary rat hepatocytes using transcriptome analysis. Total RNA was isolated from hepatocytes with and without 24 h of NGF exposure, and subjected to RNA enrichment by PCR and RNA sequencing procedures. Comparison of transcriptome profiles between control and NGF-stimulated hepatocytes demonstrated that NGF significantly up-regulated 10 genes and down-regulated 23 genes in hepatocytes. Subsequent KEGG pathway enrichment analysis indicated that NGF significantly affected the retinol metabolism pathway via increased retinol dehydrogenase 16 (RDH16) expression. In a mouse model of bile duct ligation-induced cholestatic liver injury, NGF supplementation significantly enhanced RDH16 expression, whereas administration of anti-NGF neutralizing antibodies prominently decreased RDH16 expression in cholestatic livers, supporting the positive role of NGF in the regulation of RDH16 in diseased livers. In vitro study further demonstrated that NGF triggered de novo synthesis of RDH16 in primary rat hepatocytes, mainly through an NF-κB signaling pathway. In conclusion, this study demonstrates the up-regulation of RDH16 by NGF in cultured rat hepatocytes and mouse cholestatic livers, and provides novel insights on the mechanistic role of NGF in the retinol metabolism of livers.